2014
DOI: 10.1111/fwb.12363
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication decreases distance decay of similarity in diatom communities

Abstract: Summary The distance–decay relationship has been claimed to be a predictor for biological diversity because it unites several ecological phenomena such as dispersal ability and environmental structure. The effect of long‐term disturbances on distance decay, however, has been widely overlooked, especially for microorganisms. We examine the effect of eutrophication on the distance–decay relationship in communities of attached diatoms in three peatland areas: mesotrophic, eutrophic and hypertrophic. The study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 53 publications
7
26
0
Order By: Relevance
“…In contrast, the Pogonia stream is surrounded by ~480 ha of undeveloped oak-hickory forest, and is subject to much lower human impact. This finding agrees with other studies indicating that ecosystems that are highly im pacted by human activity tend to display lower biodiversity compared to less impacted areas (Rodrigues et al 2013, Goldenberg Vilar et al 2014). Recent studies have indicated that this trend extends to microbes including bacteria and fungi (Kebli et al 2012, Rodrigues et al 2013, and one previous report suggested that viral richness is likewise impacted (Fancello et al 2013).…”
Section: Comparison Of Lake Matoaka Viral Metagenomessupporting
confidence: 93%
“…In contrast, the Pogonia stream is surrounded by ~480 ha of undeveloped oak-hickory forest, and is subject to much lower human impact. This finding agrees with other studies indicating that ecosystems that are highly im pacted by human activity tend to display lower biodiversity compared to less impacted areas (Rodrigues et al 2013, Goldenberg Vilar et al 2014). Recent studies have indicated that this trend extends to microbes including bacteria and fungi (Kebli et al 2012, Rodrigues et al 2013, and one previous report suggested that viral richness is likewise impacted (Fancello et al 2013).…”
Section: Comparison Of Lake Matoaka Viral Metagenomessupporting
confidence: 93%
“…Land use proved an important spatial factor explaining the variance in community composition, suggesting that agricultural practices can affect spatial β-diversity as grassland and bulb ditches had lower median β-diversity than the dune ditches. This concurs with other studies showing that spatial β-diversity can decrease with increasing disturbance in a wide array of organisms (Goldenberg Vilar et al, 2014;Johnson & Angeler, 2014;Karp et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…This concurs with other studies showing that spatial β-diversity can decrease with increasing disturbance in a wide array of organisms (Goldenberg Vilar et al, 2014;Johnson & Angeler, 2014;Karp et al, 2012). This concurs with other studies showing that spatial β-diversity can decrease with increasing disturbance in a wide array of organisms (Goldenberg Vilar et al, 2014;Johnson & Angeler, 2014;Karp et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…, Goldenberg Vilar et al. ). The most striking direct effect of eutrophication on animal communities stems from large increases in benthic biomass, which in turn can lead to precipitous declines in dissolved oxygen concentrations following senescence and decomposition in the basal compartment (Carpenter et al.…”
Section: Introductionmentioning
confidence: 99%